2020
DOI: 10.1007/s12350-018-1415-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of ischemic electrocardiographic changes with regadenoson stress myocardial perfusion imaging

Abstract: Regadenoson-induced ischemic ST↓ is more common in women and it provides a modest independent prognostic value beyond MPI and clinical parameters. ST↓ ≥ 0.5 mm is a better threshold than ≥ 1.0 mm to define ECG evidence for regadenoson-induced myocardial ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…They found C 0.5 mm of ST depression to predict cardiac death, non-fatal MI, and coronary revascularization in patients with abnormal or normal MPI, if adjusted for clinical and other imaging factors. 1 Among those in the subgroup of patients with greater ST depression, C 1.0 mm, ST depression was not predictive. Fewer patients were in the latter group, 133 vs 89 with C 0.5 mm, making this latter finding likely secondary to the smaller sample size.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…They found C 0.5 mm of ST depression to predict cardiac death, non-fatal MI, and coronary revascularization in patients with abnormal or normal MPI, if adjusted for clinical and other imaging factors. 1 Among those in the subgroup of patients with greater ST depression, C 1.0 mm, ST depression was not predictive. Fewer patients were in the latter group, 133 vs 89 with C 0.5 mm, making this latter finding likely secondary to the smaller sample size.…”
mentioning
confidence: 92%
“…Investigators who examined ST depression in the setting of abnormal perfusion have found such patients to have more extensive CAD and a worse prognosis than those without ST depression. 1,5,6,[14][15][16] Intuitively, ST depression in patients undergoing vasodilator stress with normal perfusion would also be predictive. This is unless the perfusion images trump ECG response.…”
mentioning
confidence: 99%
“…For example, a CACS of zero may affirm low risk of a ''borderline'' MPI result due to an artifact or discrepant data between the stress electrocardiography and MPI conclusions. 17 On the other hand, very high CACS C 1000 may raise suspicion of multivessel CAD in symptomatic patients with an apparently normal MPI due to ''balanced ischemia''. Importantly, elevated CACS in patients with normal MPI would prompt an earlier focus on aggressive risk factors modification and initiation of statin and aspirin therapies.…”
mentioning
confidence: 99%
“…2 Doukky and colleagues have also recently suggested the potential of lowering the ECG threshold for abnormal ST depression during vasodilator stress to [ 0.5 mm of flat or horizontal ST depression. 9,10 In this issue of the Journal, Balfour, Bourque, and colleagues at the University of Virginia explore a new opportunity to improve exercise test sensitivity by quantifying the subtle changes that occur in the propagation of the wavefront of depolarization as it moves through areas of ischemic myocardium. 11 Building on the work of earlier investigators, these authors found that incorporating an assessment of these high frequency, low amplitude signals that occur during the QRS complex to standard 1 mm of ST depression criteria increased test sensitivity to detect ischemia as assessed by MPI, improved the prediction of outcomes over a 5.3 years of follow-up and added to the prediction of patients who would be referred for early revascularization.…”
mentioning
confidence: 99%